PERENCANAAN PENGGUNAAN AIRBAG UNTUK MENAIKKAN DAN MENURUNKAN KAPAL DALAM RANGKA REPARASI KAPAL TANKER 304 GT DI PT.DOK DAN PERKAPALAN KODJA BAHARI GALANGAN III - Calvin Mohammed Nirsan Junior (2022)
Technological developments in the shipping world lately are rapidly developing, one of which is the use of airbag systems or airbags. It is a system as a means for launching and a means to get on and off ships that will or have been repaired or new buildings. The airbag system was first used on January 20, 1981 at xiao qinghe shipyard in jinan city of shangdong province of China. Some shipyards in Indonesia already use airbags as a means for launching ships that have been built, besides that airbags are also used as a means to raise ships to be repaired and lower ships The need for the use of airbags for various types of ships is different. The difference in the use of airbags for ship type types is greatly influenced by the weight of the ship, the length of the keel, the shape of the ship's base and the length of contact between the airbags and the ship's base (Ld). In the equation of calculating the need for the use of airbags, in addition to the weight factor of the ship, the length of contact between the airbags and the hull (Ld) also greatly affects, because Ld is a dividing factor in the calculation. This writing aims to find out the launch of the ship using an airbag system. It was found that a case study in a ship where there was structural fatigue (fatigue) this became one of the failures that caused the ship to be damaged. In this study explained in terms of planning in the use of airbags for the repair of 304 GT tankers at PT. Docking and Shipping Kodja Bahari Galangan III, namely preparations in the context of using airbags on the 304 GT tanker, steps in the use of Airbags, The process of preparing ship repairs and there are impacts that can be obtained if there are delays from the shipyard and ship owners. Keyword : Airbag, Ship Repair.